Modal and Harmonic Response Analyses of the Kenyir Dam Intake Section - Arbain A.; Mazlan A.Z.A.; Zawawi M.H.; Radzi M.R.M. (Springer, 2023)
Finite element method; Frequency response; Modal analysis; Natural frequencies; Dynamic behaviors; Frequency response functions; Harmonic response; Harmonic response analysis; Induced vibrations; Intake section; Maximum deflection; Mode shapes; Harmonic analysis